PENGARUH LITERASI EKONOMI DAN LINGKUNGAN SOSIAL TERHADAP MINAT BERWIRAUSAHA MAHASISWA PENDIDIKAN EKONOMI FKIP UNTAN - Haliza Sastri; Nuraini Asriati; Husni Syahrudin (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
Indonesia's entrepreneurial need ratio is 4% while the entrepreneurship ratio in November 2021 is 3.1%, there is a 0.9% shortfall of the total population of 260 million people. The importance of entrepreneurship includes being one of the sources of income for the country's economy, as a means of absorbing labor and fostering a spirit of independence. In fact, the educational environment, especially students, is still oriented to become employees of both ASN and private employees because of the guarantee of a fixed income. Kasmir research shows that only 20% of 500 students choose to become entrepreneurs after completing their studies. Isti's research results showed that only 8 people out of 20 students of Economics Education FKIP Untan in 2016 were the research samples who chose entrepreneurship. No more than 50% who choose entrepreneurship. In accordance with the results of the study, it was said that the student's interest in entrepreneurship was still very low. The results of the questionnaire distribution to a sample of 86 people using a Likert scale were analyzed using the multiple regression method. The results showed that economic literacy and social environment had a positive influence on the interest in entrepreneurship, either partially or simultaneously. This research can be the basis for further research to explore other factors that can encourage students' interest in entrepreneurship